Comparative assessment of enamel remineralisation on the surface microhardness of demineralized enamel - an in vitro study - Bhavsar, Bhavika; Vijo, Mary; Sharma, Pranjely; Patnaik, Tulika; Alam, Mohammad Khursheed; Patil, Santosh (PeerJ, 2022)
Objective The main objective of the study was to compare two different remineralising materials containing casein phosphopeptide-amorphous calcium phosphate, bioactive glass on enamel surface microhardness. Materials and Methods Thirty premolars were used for specimen preparation. Group 1 (the control group) consisted of intact enamel samples, group 2: CPP-ACPF (Tooth Mousse Plus), group 3: bioenamel remineralising gel (Prevest DenPro). All specimens were subjected to demineralisation except the control group, followed by which remineralising agents were applied. A universal hardness tester was used to assess the surface microhardness of all samples. Results were analysed using one-way ANOVA test and comparison was analysed using Scheffe’s post hoc least significant difference (LSD) test. Results Both remineralising agents used in groups 2 and 3 have shown significant outcome in terms of improving the surface microhardness in comparison with the control group. Group 2 increased the enamel hardness by 8.34 where P = 0.023 whereas group 3 increased the hardness by 5.87, where P = 0.01. Conclusion Group 2 has a superior hardness value than group 3; however, no statistically significant results were obtained between both the groups.
Keywords: Carious lesions; Microhardness; Fluoride; Remineralisation; Bioglass; Hydroxyapatite; Calcium phosphate; Demineralisation